INTEGRATED ANALYSIS OF RESERVOIR PROPERTIES HETEROGENEITY ON ISOLATED CARBONATE BUILDUP OF PRE-PARIGI FORMATION IN MAHES FIELD NORTHWEST JAVA BASIN - Sobani
Mahes field was discovered in 1993 and proved its hydrocarbons presence after Drill Stem Test (DST) with a gas production rate of 9 MMSCFD. Mahes field has not been developed yet since discovered due to the absence of integrated study to figure out the heterogeneity distribution of reservoir properties. The objectives of this study are to characterize and identify heterogeneity of reservoir properties isolated carbonate by integrating analysis facies association, stratigraphic sequence, and rock typing to build reservoir model. This field has only one exploration well Mahes-1, to analyze reservoir characterization are optimized by utilizing 3D seismic data and comprehensive interpretation well data. Data used in this study includes well log (gamma ray, resistivity, neutron, and density), core (58 ft), petrography (14 samples), routine core (46 samples), and special core analysis (8 samples). Seismic data which consist of depth structure map and seismic attribute. These data play important roles to distribute reservoir properties in reservoir modeling. The heterogeneity of isolated carbonate is influenced by facies diversity, facies distribution, carbonate growth which is correlated with sea-level fluctuation and diagenesis. Four analysis steps are undertaken in this study. Firstly, evaluation of facies association based on core and petrography description. Secondly, stratigraphic sequence analysis by applying seismic stratigraphy interpretation and chronostratigraphy methods. Thirdly, rock type analysis utilizing Winland R35 method, and finally, comprehensive integration of the previous analyzes as a foundation in building isolated carbonate reservoir model by applying geostatistics method to obtain comprehensive result. There are five groups of facies association including, open shelf, forereef slope, reef core, back-reef lagoon outer and back-reef lagoon inner. Showing three sequences of carbonate development in study area, dominant growth process is occurred on the Highstand System Tract (HST) and identified three Sequence Boundaries (SB). Sequence Boundary (SB) area usually have good reservoir properties because diagenetic process intensively occurs and triggering the development of secondary porosity. Anlysis of reservoir property quality is conducted using Winland R35 rock typing method, generating RT-1, RT-2, RT-3, RT-4, and RT-5. RT-1 is the best rock type, as it is dominated by lithofacies bioclastic packstone with intensive vuggy features and deposited in the back-reef lagoon outer area. The outcome of integrated isolated limestone model shows that the best distribution of reservoir properties is in zone 2 and zone 4. The zones are located in the back-reef lagoon outer and area around the Sequence Boundary (SB), where the intensive vuggy dominantly occurred. This study proves that the heterogeneity of isolated carbonate was influenced by the diversity, distribution of facies, carbonate growth process and diagenesis. The integration process of isolated carbonate modeling can show the distribution of reservoir property heterogeneity spatially, either vertical or lateral, to be later utilized in Mahes field development.